2008
DOI: 10.1093/ajcn/88.4.1104
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycemic index and the risk of age-related macular degeneration

Abstract: Background: Dietary factors are known risk factors for age-related macular degeneration (AMD)-the leading cause of visual loss among persons aged ͧ65 y. High-glycemic-index diets have been hypothesized as a risk factor for AMD, but prospective data are unavailable. Objective: The objective was to examine the association between dietary glycemic index and the 10-y incidence of AMD in the Blue Mountain Eye Study population. Design: This was a population-based cohort study with 3654 participants (ͧ49 y) examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 50 publications
1
59
0
1
Order By: Relevance
“…Even synaptic pruning is affected by the switch to the LG diet. As such, the data support human epidemiologic observations that suggest that consuming lower GI diets is associated with delayed progress of early AMD (7)(8)(9). The higher levels of AGEs and autofluorescence in HG mice and their delayed or arrested accumulation in LG or HGxoLG mice indicate that the benefit of the LG diet is derived in part from lower glycative stress.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Even synaptic pruning is affected by the switch to the LG diet. As such, the data support human epidemiologic observations that suggest that consuming lower GI diets is associated with delayed progress of early AMD (7)(8)(9). The higher levels of AGEs and autofluorescence in HG mice and their delayed or arrested accumulation in LG or HGxoLG mice indicate that the benefit of the LG diet is derived in part from lower glycative stress.…”
Section: Discussionsupporting
confidence: 78%
“…Stresses associated with AMD include environment, age, and genetics (3). Frustratingly, there are no early biomarkers to anticipate AMD, and there are no therapies or cure.Recently, we and others observed in epidemiologic studies that, in addition to micronutrients (4-6), macronutrient quality [e.g., consuming a diet with a high glycemic index (GI)] is a significant risk factor for AMD onset and/or progress in nondiabetic humans (7)(8)(9). The GI appears to be an attractive dietary intervention target, because simple replacement of small amounts of high-index foods (such as white bread) with lower-index foods (such as wholegrain bread) can significantly reduce glycemic peaks without requiring a change in overall dietary patterns (7).…”
mentioning
confidence: 99%
“…Due to the limitation of experimental instruments, we did not statistically assess other risk factors, such as oxidant intake and sun exposure. In addition to these environmental influences, systemic diseases or changes in body indexes (such as elevated BMI and C-reactive protein levels) may also be risk factors for eye diseases (Kaushik et al, 2008;van de Ven et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ströhle & Hahn confirmed that the energy derived from CHOs -despite being dependent upon geographic latitude and ecological environment -in modern hunter-gatherers is markedly lower than in Westernized societies [10]. High CHO intake, in particular in the form of sugar and other high GI foods, has been linked to modern diseases like metabolic syndrome [11], Alzheimer's disease [12,13], cataract and macula degeneration [14][15][16] and gout [17]. Intriguingly, with the possible exception of Alzheimer's disease [18], the occurrence and prognosis of cancer seems positively associated with both the prevalence of these diseases [19][20][21][22][23][24][25][26][27][28] and the GI and glycemic load (GL) of the diet [29][30][31][32]; this implies a possible role of high CHO intake in cancer as well.…”
Section: Modern Hunter-gatherers' Dietmentioning
confidence: 99%